2016
DOI: 10.1002/jcph.768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disease Pathologies on Transporter Expression and Function

Abstract: Transporters are important determinants of drug absorption, distribution, and excretion. The clinical relevance of drug transporters in drug disposition and toxicology depends on their localization in liver, kidney, and brain. There has been growing evidence regarding the importance of disease status on alterations in metabolizing enzymes and transporter proteins. This review focuses on uptake and efflux transporter proteins in liver, kidney, and brain and discusses mechanisms of altered transporter expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 142 publications
0
32
0
2
Order By: Relevance
“…In addition, the cumulative biliary excretion of cefdinir and the cumulative urinary excretion of cefditoren had been detected, and the levels were almost zero in this study. Moreover, it was not completely clear whether the expression of PEPT would be changed in the AKI morbid condition . More detailed and specific investigation needed to be clarified in the future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the cumulative biliary excretion of cefdinir and the cumulative urinary excretion of cefditoren had been detected, and the levels were almost zero in this study. Moreover, it was not completely clear whether the expression of PEPT would be changed in the AKI morbid condition . More detailed and specific investigation needed to be clarified in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression and function of renal transporters would be changed under the condition of AKI. However, the current research on this aspect was extremely limited and it still needed further investigation …”
Section: Introductionmentioning
confidence: 99%
“…It is responsible for excreting soluble metabolic waste products and pharmaceutical drugs, maintaining normal biological functions, and secreting hormones and enzymes [9][10][11][12]57]. Numerous global gene expression studies involving diseased kidney have identified sex differences in several functions performed by the kidney, such as glomerular filtration, tubular secretion, and tubular reabsorption [6,58].…”
Section: Discussionmentioning
confidence: 99%
“…Nossos resultados estão em concordância com a literatura que indica a manutenção ou aumento da expressão de MRP2 no carcinoma hepatocelular. (135,137,(154)(155)(156)(157) A ausência de variação da expressão de MRP2 em relação ao número, tamanho dos nódulos, padrão arquitetural (inclusive os sólidos), e grau de diferenciação (inclusive os menos diferenciados) de CHC sugere que a proteína MRP2 apresenta-se altamente expressa no CHC independentemente das variáveis anatomopatológicas analisadas. Desta forma, a escassez de informações e a presença de resultados divergentes sobre a avaliação da expressão desta proteína nos adenocarcinomas de ductos biliares conduzem a necessidade de ampliação da investigação desta proteína transportadora nos colangiocarcinomas.…”
Section: Discussão 154unclassified
“…A principal função desta proteína ABC está relacionada ao transporte de compostos orgânicos e sais biliares conjugados bivalentes, podendo estar super expressa em condições colestáticas. (34,157) No presente estudo, apenas 14 (17,5%) dos 80 CHC avaliados mostraram-reação positiva com o anticorpo MRP3 (DTX1), exibindo distribuição basolateral em mais de 10% dos hepatócitos tumorais.…”
Section: -Mrp3 -Proteína 3 Associada à Resistência à Múltiplas Drogasunclassified